Athapahariyas: A Geographical Perspective - Khatiwada, Shambhu Prasad (NUTA Journal, 2019)
Cultural geography attempts to real-life situations of Athapahariyas in Dhankuta district. Their sense of place bring to where they live, how they shape their way of living to respond in this place. their socio-economic and political changes are also reshaped by the place or surrounding habitat. In this context, this effort is made a valuable literature for detailed socio-economic and cultural studies as a lane of folklore geography with concerning theories of sense of place. The main objective of this paper is to analyse some aspects of the Athapahariyas and seeks to answer meaning of places as an aspect of environmental experiences.